Cutting edge: in contrast to effector T cells, CD4+CD25+FoxP3+ regulatory T cells are highly susceptible to CD95 ligand- but not to TCR-mediated cell death - Fritzsching, Benedikt; Haas, Jürgen; Wildemann, Brigitte; Krammer, Peter H.; Suri-Payer, Elisabeth (The journal of immunology, 2005)
CD4+CD25+FoxP3+ regulatory T cells (Treg) suppress T cell function and protect rodents from autoimmune disease. Regulation of Treg during an immune response is of major importance. Enhanced survival of Treg is beneficial in autoimmune disease, whereas increased depletion by apoptosis is advantageous in cancer. We show here that freshly isolated FACS-sorted Treg are highly sensitive toward CD95-mediated apoptosis, whereas other T cell populations are resistant to CD95-induced apoptosis shortly after isolation. In contrast, TCR restimulation of Treg in vitro revealed a reduced sensitivity toward activation-induced cell death compared with CD4+CD25− T cells. Thus, the apoptosis phenotype of Treg is unique in comparison to other T cells, and this might be further explored for novel therapeutic modulations of Treg.